A study of sleep problems and its associated factors among patients presenting in psychiatry OPD at tertiary-level hospital in Nepal - Paudyal, Sreya; Shah, Sanjeev; Ranjan, Sanjeev; Subedi, Sandip (Journal of Psychiatrists' Association of Nepal, 2023)
Background: Sleep disturbances amongst those with psychiatric disorders are quite common and may occur as a primary disorder or in association with any psychiatric disorders. The aim of this study is to find out the prevalence of sleep disorders and its associated factors in psychiatric outpatients. Material & Methods: This cross- sectional study was conducted among the patients presenting in the psychiatric opd, from 1st Feb 2022 to 30th July, 2022 in tertiary level hospital in Nepal. Total 217 samples were included and purposive sampling technique was applied for sample collection. After written informed consent from participants socio-demographic data were collected. Athens Insomnia scale (ASI) and Screening symptoms of sleep disorder(s) were the tools applied to the participants to find out types of sleep disorders. Results: In our study, sleep disorders were found in 66.8% of the patients presenting to psychiatric opd. Insomnia was the most common finding accounting for 59.4 % of the participants. Narcolepsy was found in 2.3% whereas parasomnia was found in 5.1 %; periodic limb movement disorder/Restless leg syndrome (PLMD/RLS) in 5.1%; disturbed circadian rhythm was found in 3.7% and Sleep Related Breathing Disorder was found in 5.1% of the participants. Patients diagnosed with mood disorder (80.4%) and primary headache disorders (82.9%) had more sleep problems compared to other diagnosis. Conclusion: This study was the first in Nepal to assess the prevalence of sleep disorders in psychiatric outpatients. Our study emphasis importance of careful evaluation of sleep problems for proper management of the psychiatric patients.